Relationship between Accounting Comparability and Accrual-based and Real Earnings Management - Mohammad Omid Akhgar (Ph.D) (Shahid Bahonar University of Kerman, 2019)
Objective: Earnings are one of the most important factors influencing economic decisions, so corporate executives may manage the earnings to show stability in improvements and efficiency. Managers can manipulate the earnings by choosing discretionary accruals or regulating company's actual activities. If the accounting system of a company and its results are comparable, managers' motivation for opportunistic behavior of earnings management reduces, and as a result, external users can analyze the company's actual economic performances more accurately. The purpose of this study is to investigate the relationship between accounting comparability and the accrual-based earnings management, and then, the result for real earnings management in the companies listed in the Tehran Stock Exchange, TSE. Methods: This research is an applied study and the correlation-based in the nature. The sample consists of 122 firms in the TSE in the years 2011 to 2015, chosen by the systematic deletion method of sampling to reach the main sample. To examine the relationship between variables, multiple regression and generalized least squares methods were used. Results: The results showed that when the company's accounting system provides comparable figures, the company's accrual-based earning management decreases, and so managers to handle their earnings manipulate their real activities, which lead to increase in real earnings management. Conclusion: Based on the results of the research, firms' managers are recommended to pay more attention to the comparability of financial statements due to its importance in earnings management.